Integrative psychotherapeutic intervention in a case of cellotipia - Pacheco-Miranda, Aarón Israel (Consorcio de Universidades Mexicanas A.C., 2017)
This case study aims to intervene in a case of cellotipia from a "integrative approach of technical integration of orientation and theoretical integration broad", combining the cognitive-behavioral and psychodynamic approaches with the clinical case study modality. The diagnosis was made using techniques from both approaches, including the Machover projective tests and the Test of the figure in to the rain and the questionnaire of maladaptive schemes, as well as the Diagnostic and Statistical Manual of Mental Disorders DSM-V (APA, 2013). Thirty therapeutic sessions were performed; psychogenic factors were found that explained the appearance and maintenance of cellopathy symptoms. The intervention was performed integrating both streams to the service of the patient with positive results, the remission of the majority of the reported and inferred symptoms was achieved and awareness of the underlying causes of its cellotipia, as well as stop the congnitions that kept it.